Perceptions of Students with Disabilities on Reasonable Accommodation at a Tertiary Education: A Case of a Rural University in Limpopo Province, South Africa - Mukwevho, M.H.; Gadisi, A. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
The advent of democracy in South Africa has put initiatives to redress social injustice suffered by women and people with disabilities. Enrollment of students with disabilities at universities increases yearly, influencing an increase in buying of assistive technologies to enable a teaching and learning environment. This paper explores the perceptions of students with disabilities on the role of reasonable accommodation in terms of accessibility and facilitation of teaching and learning at the university based on the human rights approach. A pre-corvid 19 pandemic survey used a convergent parallel mixed-method design to evaluate perceptions of reasonable accommodation on the campus. Both quantitative and qualitative data were collected roughly simultaneously and integrated into the interpretation of the overall results. A focus group comprised of the representatives of students with disabilities was interviewed. The surveyed population comprised all students with disabilities between the ages of 18 to 25 registered with the Disability Support Unit (DSU) of the University of Venda. The questionnaires collected reasonable accommodation perceptions and satisfaction rates from students about organizational support and training. The distributed questionnaires produced a 90% response rate. The findings highlighted that students with disabilities encountered barriers of inaccessibility to classrooms and residents. Adequate learning material is a barrier for students with visual disabilities. Institutional budget and item costs render buying assistive technologies and building new infrastructures for students with disabilities a constraint. Policy and practice in the institution remain a limitation to interfacing education and disability smoothly.